Biomechanical and physiological effects of an upper-body exoskeleton during simulated load-carrying on an inclined surface - Gabriela Garcia; Rafaella Yañez; Milena Espoz; Camilo Albuja; Paul G. Arauz; Bernard J. Martin (PLoS ONE, 2025)
Objective This study assessed the effects of a passive upper-body exoskeleton (CarrySuit®) on heart rate, muscle activity, and kinematics while carrying 12 kg box on a 12° inclined treadmill. Background Various passive exoskeletons designed for commercial use have emerged on the market, aiming to support lifting and carrying tasks. However, their effects on biomechanical metrics while walking on inclined surfaces are not yet conclusive. Method Thirty participants carried a 12 kg box with and without the exoskeleton while walking on a treadmill with a 12° incline. Whole-body kinematics, heart rate, and muscle activity in the low back, legs, and arms were evaluated in each condition. Results The exoskeleton significantly (p < .05) reduced peak erector spinae, biceps brachii activity, and heart rate across sexes, with medium to large effect sizes (ηp2 > 0.1). A decrease in mean erector spinae activity was observed in males only. However, for all, the exoskeleton increased vastus lateralis activity while reducing gastrocnemius activity, with medium effect sizes (ηp2 = 0.1). Kinematically, it led to increased dorsiflexion and knee flexion, with sex-specific adaptations such as reduced pelvic tilt in males and greater thorax tilt in females, with small to medium effect sizes. It also promoted a more neutral neck posture and altered hip asymmetry patterns. Conclusion These findings suggest that the CarrySuit® effectively alters heart rate, muscle activity and joint movements during inclined load-carrying tasks, with more benefits shown for males than females. This research contributes to the scientific understanding of commercial exoskeleton technology’s efficacy in carrying tasks.